Frequency of guideline‐defined cow's milk allergy symptoms in infants: Secondary analysis of EAT trial data. Issue 1 (7th December 2021) - Vincent, Rosie; MacNeill, Stephanie J.; Marrs, Tom; Craven, Joanna; Logan, Kirsty; Flohr, Carsten; Lack, Gideon; Radulovic, Suzana; Perkin, Michael R.; Ridd, Matthew J.
Abstract: Background: Non‐IgE‐mediated Cow's Milk Allergy (CMA) has a prevalence of less than 1% in children. Guidelines developed to help non‐specialists diagnose CMA may lead to misattribution of normal symptoms and contribute to overdiagnosis of CMA. We sought to establish the frequency of symptoms during infancy associated with non‐IgE‐mediated CMA, using the international Milk Allergy in Primary Care (iMAP) guideline as representative of CMA guidelines more generally. Method: Secondary analysis of the Enquiring About Tolerance (EAT) randomized controlled trial (ISRCTN 14254740; 1303 exclusively breastfed 3‐month‐old healthy infants). Key outcomes were ≥2 iMAP symptoms associated with 'mild‐moderate' and 'severe' non‐IgE‐mediated CMA. Results: Whilst breastfeeding and parental atopy rates were higher than the general population, participants were otherwise similar to the population of England and Wales. Two or more non‐IgE CMA symptoms were reported by 25% families for mild‐moderate and 1.4% for severe symptoms each month between ages 3 and 12 months, peaking at 38% with ≥2 mild‐moderate and 4.3% ≥2 severe symptoms at three months, when participants were not directly consuming cow's milk. 74% of participants reported ≥2 mild‐moderate symptoms and 9% ≥2 severe symptoms in at least one month during this period. At six months there was no evidence of difference in the proportion of children with ≥2 symptoms between those consuming (29.5% mild‐moderate, 1.8% severe) and not consuming cow's milk (35.3% mild‐moderate, 2.2% severe). Mean monthly reporting of ≥2 symptoms was also no different between those with (15.8% mild‐moderate, 1.1% severe) or without eczema at baseline (16.7% mild‐moderate, 1.3% severe). Conclusions: Guideline‐defined symptoms of non‐IgE‐mediated CMA are very common in infants. Guidelines may promote milk allergy overdiagnosis by labelling normal infant symptoms as possible milk allergy. Abstract :